Fenomena Khalwat Pasca Khitbah di Masyarakat Desa Bluto Kabupaten Sumenep - Sofia, Sofia Mubarokah Sa'bana (Prodi Ilmu Hadis Fakultas Ushuluddin dan Dakwah Institut Agama Islam Negeri Madura, 2023)
This research aims to examine the phenomenon of khalwat that often occurs in society where the engagement phase is the first step of taaruf before entering marriage. During this period there are other things that must be considered by the prospective bride and groom and their parents, namely regarding the ethics of association during the khitbah (engagement) period. The ingredients in the customary practice of the engagement community are considered as cultural legality where the prospective spouses have considered mahrom with khalwat (to be alone) which is allowed by their parents. Although in reality this is wrong because it violates islamic law. This article explains the khalwat phenomenon that occurs in commuity, especially in Bluto village, Sumenep Regency. This reseach is included in empirical legal research methods. As for the primary data sources, they were obtained directly from the public through an interview process and secondary data were sourced from literacies in books, jounals, articles, and hadith related to the theme of this article. Data collection techniques se have khalwat with the opposite sex who are not mahram (fiance) considered normal as a form of introduction or approach to mutual understanding between partners before entering into marriage as long as this is still at a reasonable stage and when viewed from a hadith perspective and the Al-Qur’an seclusion with non-mahrams is not permissible or unlawful even if the status has been preached.